Pelaksanaan Hafazan Dalam Program Ulul Albab Berdasarkan Jantina Dan Kumpulan - Siti Suriyani Binti Sulaiman; Ahmad Yunus Bin Kassim (ILIN Institute Makassar, 2018)
This article aims to review the implementation of the hafazan in the Ulul Albab program based on gender and the group. The implementation of the hafazan is reviewed from the aspect of time allocation and preparation of the student before performing the Quran recitation. This study involved 120 Form One students at MRS Gemencheh. In conducting this study, several Islamic Education teachers were involved as instructors and mentors for the Tahdhir, Murajaah and Tasmik sessions. A pilot study found that the whole item was at a high level of reliability above 0.8. The findings show that there is no significant difference and interaction effect of time allocation for students in performing the hafazan. Furthermore, the findings show that there is a significant difference in the time allocation of students in performing hafazan based on gender. For students preparation before performing the hafazan, there is no difference and significant interaction effects based on gender and group. Student preparation before performing the hafazan and time allocation is one of the factors that support student achievement.